Práticas pedagógicas interculturais de docentes na Educação Básica e no Ensino Superior: análise da produção acadêmica brasileira - Barbosa, Ana Maria da Silva (2022)
The theme of this research is related to teachers' intercultural pedagogical practices in Basic and Higher Education, considering the problem involving the inequality present in schools - especially public ones - and the following need for the development of such practices. The question of the research is: how is the Brazilian academic production on interculturality configured in the pedagogical practices of teachers who work in both Basic and Higher Education? Thus, the general objective delimited is: to analyze the relations between interculturality and teaching in the pedagogical practices of Basic and Higher Education teachers, by carrying out a bibliographic survey of the Brazilian academic production available in journals in the educational field. The specific objectives established are: to investigate what has been published about the intercultural pedagogical practices of teachers in Basic Education and Higher Education; and to verify which contributions the analysis of intercultural pedagogical practices offers for the construction of new perspectives of work with intercultural education in the contexts of Basic and Higher Education. The theoretical framework is supported by humanizing education and interculturality theories. After collecting data from Brazilian journals in the field of Education, selected from pre-established descriptors, the corpus of the research analysis was composed of 8 articles considered "core" (about 33% of the selected articles), among them, only three dealt with intercultural pedagogical practices in Basic Education and five in Higher Education. The remaining 16 articles discussed: theoretical and conceptual approach on intercultural pedagogical practices; intercultural practices developed with artistic groups; and intercultural practices carried out in commercial relations between the indigenous community and the non-indigenous collective organization. It was verified that the initiatives with intercultural pedagogical practices present elements that can benefit and enhance the implementation of teaching practices that value cultural differences. In this aspect, the relationship between interculturality and teaching can be announced positively when relating to the presence and articulation of the contents domains, methodologies, and sensibility in the teaching practices addressed in the articles - theoretical categories which we used to accomplish the analyses. Regarding the contents, the respect for the students' knowledge was a constant; regarding the methodologies, we noticed that they were not based on "talking about", but always involved acting with the students from their realities and thinking about this action; as for the sensibility, it was analyzed that the articles did not offer subsidies to discuss the sensibility as to the principle that the teachers need to be committed with the learning of all students; it (sensibility) was always found in its relation with the contents and the methodologies. We also presented the contributions that the results provided regarding the reflection on teaching practices based on the valorization and dialogue between different cultures, indicating pedagogical possibilities concerning the relationship between interculturality and teaching.